Penggunaan Kecerdasan Buatan dalam Pendidikan dan Dakwah : Tinjauan Hukum Islam dan Keputusan Tarjih Muhammadiyah - Izzah, Imroatul Khuluqi; Aziz, Muhammad Abdul; SW, Oman Fathurohman (Al-Mau’izhoh: Jurnal Pendidikan Agama Islam, 2025)
This article examines the normative status of artificial intelligence (AI) in Islamic education and da’wah with a specific focus on Muhammadiyah’s Tarjih decisions. It addresses how the use of AI in teaching and preaching should be judged within Islamic law and in what ways Muhammadiyah’s official documents can serve as a basis for operational guidelines. Using a normative conceptual, library-based design, the study analyzes contemporary fatwas on AI, key Muhammadiyah texts such as PHIWM, Manhaj Tarjih, and Tanfidz Keputusan Muktamar ke-48, as well as more than fifteen peer-reviewed articles on AI in Islamic education, digital da’wah, and maqāṣid al-syarīʿah. Data are processed through content analysis and normative analysis in order to extract central themes and derive legal and ethical principles. The findings indicate that AI is generally mubāḥ as a wasīlah whose ruling follows its purpose and mode of use. It may become mandūb when it expands access to knowledge and supports Islamic education and da’wah, but can be makrūh or ḥarām when it enables plagiarism, misinforms religious audiences, erodes critical thinking, or violates privacy. The study formulates five core principles for Muhammadiyah institutions, covering tawḥīd and scholarly trustworthiness, maslaḥah and harm prevention, justice and non-discrimination, adab and academic integrity, and supervision by qualified ulama and official bodies. The results imply the need for an official Muhammadiyah guideline on AI and for empirical follow-up research in schools and universities.